Cannabis use is associated with monocyte activation (sCD163) in patients admitted for alcohol use disorder treatment. (1st November 2020) - Fuster, Daniel; García-Calvo, Xavier; Bolao, Ferran; Zuluaga, Paola; Rocamora, Gemma; Hernández-Rubio, Anna; Sanvisens, Arantza; Tor, Jordi; Muga, Robert
Graphical abstract: Highlights: Cannabis use was frequent in this series of patients with AUD admitted for hospital treatment. Cannabis use was associated with monocyte activation measured with sCD163. Cocaine use was not associated with inflammation or monocyte activation in this series of patients. Abstract: Background: The effect of concomitant cocaine and cannabis use on monocyte activation and inflammation in patients with alcohol use disorder (AUD) is unknown. Methods: To analyze the impact of cocaine and cannabis use on levels of markers of monocyte activation (sCD163 and sCD14) and systemic inflammation (interleukin-6 [IL-6]) in AUD patients admitted for hospital treatment between 2013 and 2018. Clinical and laboratory parameters were obtained upon admission. IL-6, sCD163, and sCD14 were measured in frozen plasma samples. We performed logistic regression to detect associations between cocaine and cannabis use and markers of monocyte activation and inflammation in the highest quartile. Results: A total of 289 patients (77.5 % male) were included (median age = 50 years). The median alcohol intake upon admission was 142 g/day. The median duration of AUD was 20 years. Of the 289 patients with AUD, 76 % were active smokers, 23.1 % and 22.1 % concomitantly used cocaine and cannabis, respectively The median levels of IL-6, sCD163, and sCD14 were 4.37 pg/mL, 759 ng/mL, and 1.68 × 10 6 pg/mL, respectively. We did not detect associations between cocaine use and inflammation or monocyte activation. Cannabis use was associated with a higher odds of having sCD163 levels in the highest quartile (adjusted odds ratio = 2.34, 95 % confidence interval = 1.07–5.15, p = 0.03). Cannabis use was not associated with inflammation. Conclusion: In this series of AUD patients the concomitant use of cannabis use was associated with sCD163 levels that were in the highest quartile, consistent with monocyte activation.